A Study for the Necessity of Risk Assessment for Heavy metal Pollution in the Barada Basin, Syria - Rimah Melhem; Yoshiro Higano (European Regional Science Association (ERSA), 2003)
Manufacturing industries are blooming rapidly in Barada Basin carrying high risk to environment and human health due to generating huge amounts of heavy metals to environmental media, particularly rivers. Few studies show that concentrations of chromium, cadmium, and lead exceed the standards in down streams of rivers. Risk assessment on human health urges for immediate measures to control the emission of these metals. In this paper, we discuss the implementation of comprehensive risk management policy as an element to introduce an optimal policy to reduce water pollution and improve water quality in the Barada Basin.
Keywords: 330